Double‐stranded DNA stereoselectively promotes aggregation of amyloid‐like fibrils and generates peptide/DNA matrices. Issue 6 (November 2014) - Yamada, Masanori; Hara, Sachiko; Yamada, Tetsuya; Katagiri, Fumihiko; Hozumi, Kentaro; Nomizu, Motoyoshi
ABSTRACT: An amyloidogenic LAM‐L peptide (AASIKVAVSADR, all‐L configuration) derived from laminin promoted cell adhesion, neurite outgrowth, and angiogenesis. Here, we prepared novel matrices using double‐stranded DNA and the LAM‐L peptide. Double‐stranded DNA promoted aggregation of amyloid‐like fibrils and generated a LAM‐L/DNA matrix through electrostatic interactions between the phosphate groups of DNA and the amino groups of LAM‐L. This formation of peptide/DNA matrix depends on the Ile‐Lys‐Val‐Ala‐Val (IKVAV) sequence in the peptide, since LAM‐RM peptide (AASVVIAKSADR), which is scrambled peptide of LAM‐L, did not form a matrix with DNA. Further, LAM‐D (all‐D configuration of LAM‐L), which forms amyloid‐like fibrils and promotes similar biological activities as LAM‐L, did not form amyloid‐like fibrils with DNA, suggesting that DNA selectively interacts with the L‐configured peptide. Moreover, the LAM‐L/DNA matrices showed stronger cell attachment activity compared with LAM‐L alone, suggesting the LAM‐L/DNA matrices have potential for use as a novel biomaterial in tissue engineering. © 2014 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 465–472, 2014.